Inventory management performance in machine tool SMEs: What factors do influence them? - Rajeev Narayana Pillai (Journal of Industrial Engineering and Management (JIEM), 2010)
Small and Medium Enterprises (SMEs) are one of the principal driving forces in the development of an economy because of its significant contribution in terms of number of enterprises, employment, output and exports in most developing as well as developed countries. But SMEs, particularly in developing countries like India, face constraints in key areas such as technology, finance, marketing and human resources. Moreover these SMEs have been exposed to intense competition since early 1990s because of globalization. However, globalization, the process of continuing integration of the countries in the world has opened up new opportunities for SMEs of developing countries to cater to wider international market which brings out the need for these SMEs to develop competitiveness for their survival as well as growth. It is observed from literature that pursuing appropriate IM practice is one of the ways of acquiring competitiveness among others, by effectively managing and minimizing inventory investment. Inventory management can therefore be one of the crucial determinants of competitiveness as well as operational performance of SMEs in inventory intensive manufacturing industries. The key issue is whether Indian SMEs pursue better IM practices with an intension to reduce their inventory cost and enhance their competitiveness. If so, what are the IM practices pursued by these enterprises? What are the factors which influence the inventory cost and IM performance of enterprises? These questions have been addressed in this study with reference to machine tool SMEs located in the city of Bangalore, India.
Keywords: 650; inventory cost; machine tool; small and medium enterprises